1989
DOI: 10.1111/j.1365-2621.1989.tb03052.x
|View full text |Cite
|
Sign up to set email alerts
|

Tainting and Depuration of Taint by Lobsters (Homarus americanus) Exposed to water Contaminated with a No. 2 Fuel Oil: Relationship with Aromatic Hydrocarbon Content in Tissue

Abstract: Lobsters (Homarus americanus) were exposed to a pulse of diesel oil and held for 21 days to depurate. Taste panels revealed a highly significant difference between samples, as well as a preference for, the untreated samples at days 10 and 11. The odor of the raw treated samples differed significantly from that of the control at each of the sampling times. Cooking appeared to remove the oily odor from the raw lobster. Significantly elevated concentrations of total aromatics were found in the hepatopancreas of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…For lobsters, this results in high levels of PAHs, which can then persist over years: up to six and seven years after for the Braer [13] and Amoco Cadiz [14] oil spills, respectively. Significantly elevated concentrations of total aromatics were found in the hepatopancreas of American lobster and their decrease was measured only after 11 days of depuration [15]. Few reviews have reported the impact of hydrocarbons on lobsters during oil spills or laboratory experiments, highlighting higher mortalities or lower abundances as major impacts [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For lobsters, this results in high levels of PAHs, which can then persist over years: up to six and seven years after for the Braer [13] and Amoco Cadiz [14] oil spills, respectively. Significantly elevated concentrations of total aromatics were found in the hepatopancreas of American lobster and their decrease was measured only after 11 days of depuration [15]. Few reviews have reported the impact of hydrocarbons on lobsters during oil spills or laboratory experiments, highlighting higher mortalities or lower abundances as major impacts [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…These organisms are unsuitable for consumption until this tainting disappears, where associated delays can take from days to up to a year after exposure, depending on the species [17]. A study of Williams et al [15] observed that the odor of raw treated lobsters differed significantly from that of the control, even after 21 days of depuration; however, cooking appeared to remove the oily odor from the raw lobster. Despite the risk of diluted bitumen (dilbit) or diesel marine spills, to the best of our knowledge, there have been no studies dealing with the impacts of a dilbit spill on American lobsters and no studies on the sub-lethal impact of a marine diesel or dilbit spill.…”
Section: Introductionmentioning
confidence: 99%